Rupture of a papillary muscle of the tricuspid valve. Echocardiographic diagnosis. Issue 3 (September 1982) - Donaldson, R M; Ballester, M; Rickards, A F
Abstract : Abnormal tricuspid valve structure and motion resulting from the rupture of a right ventricular papillary muscle were visualised by two dimensional echocardiography. These findings were confirmed at operation. Two dimensional echocardiography appears to be a satisfactory method for evaluating patients with tricuspid regurgitation of sudden onset with a view to surgery.